2002
DOI: 10.1002/cncr.10718
|View full text |Cite
|
Sign up to set email alerts
|

Cervical smear interpretations in women with a histologic diagnosis of severe dysplasia

Abstract: BACKGROUND. Because most low-grade squamous intraepithelial lesions (LSIL) regress spontaneously, the appropriate follow-up of women with a cytologic diagnosis of LSIL has engendered discussion. This retrospective study was undertaken to assess the feasibility of limiting colposcopy to women with cytologic interpretations of high-grade squamous intraepithelial lesions (HSIL) in a high-risk population. METHODS. The pathology computer files (including files from January to December

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 18 publications
(25 reference statements)
3
21
1
1
Order By: Relevance
“…The highest number (17) were seen in mild dyskaryosis which turned out to be benign in histopathology (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest number (17) were seen in mild dyskaryosis which turned out to be benign in histopathology (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…As an alternative, the cytohistological correlation and discrepancy of Pap testing were measured. Many studies too have measured the accuracy of the Pap test using the same method (15)(16)(17)(18)(19)(20)(21). We report 63.2% and 36.8% for the cytohistological correlation and discrepancy of Pap smears respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of the biopsies showing discrepancies in Histology 2a vs 2b presents small areas of metaplastic atypia, difficult to fit into the CIN groups (Geng et al, 1999;Montes et al, 1999;Ng et al, 2002;Zuna et al, 2002). The discrepancy in the relative frequency of 'normals' between Histology 2a and 2b is due to the fact that in 2b the emphasis was on representativeness for the transformation zone.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, a good technique usage in DNA proof needs knowledge, standardization from the beginning of the material acquisition and its fixation, to the histochemic marker and reading from computerized equipments, to get precise diagnostics (Zuna et al, 2002). When we compared our findings with Arcuri et al (2002) and Schoolland et al (2002), we found a huge percentage of unused material, for failure to reach a proof of basic conditions, or simply having mistaken diagnostics.…”
Section: Discussionmentioning
confidence: 90%